Un pícaro moderno y fronterizo en La Travesía de Enrique de Sonia Nazario - Torres, Edgar Cota (Diálogos Latinoamericanos, 2014)
Spanish picaresque literature has an extensive literary tradition dating back to the Spanish Golden Age. While its development is associated primarily with Spain, its influence was felt in many Latin American countries, including in many texts in the past as well as in our days. The purpose of this essay is to show how Enrique´s Journey by Sonia Nazario retains many similar characteristics of the Spanish picaresque novel, while also distancing itself from this style through the use of testimonial discourse. The writer has used many techniques from new journalism in order to paint a realistic picture of the social reality related to the mass immigration of Central Americans to the United States.